Why are Some Women Politically Active? The Household, Public Space, and Political Participation in India - Pradeep Chhibber (International Journal of Comparative Sociology 2002; 43; 409, 2002)
Women in India do not participate in political life to the same extent as men. While a fair number of women turn out to vote they have little representation in legislative bodies at the national and state level. This paper attributes the limited presence of women in legislative bodies to the fact that many women are still confined to the household. Evidence to support this claim comes from an analysis of a survey that was conducted in a state of Northern India to assess which women have been able to take the opportunity to join local bodies where, one-third of all seats, are now reserved for women. The analysis suggests that even after controlling for demographic factors, only those women who have an identity that is independent of the household are likely to avail the opportunity to contest elections for local bodies. The paper then extends the findings from the Indian case to other nations by analyzing the World Values Survey and finds that similar patterns exist globally. It is women who have an identity outside the household who are more likely to be politically active.